FJER OM MULEN VED MORGENGRY: Om brugen af dyremetaforer i det danske politi - Holmberg, Lars (Tidsskriftet Antropologi, 1996)
Lars Holmberg: The Use of Animal Metaphors in the Danish Police From within the framework of international research on the police, especially the notion of “real policework” and the categorisation of citizens, this article discusses the views on society held by the Danish police. The population of Denmark is percieved by the police to be divided between “customers” (i.e. criminals) and “good Danish citizens”. The border between these categories is maintained partly by applying animal metaphors to the customers, thereby strengthening the notion of criminality as being of animal nature. The article discusses the use of metaphors and the hierarchy that is revealed in police notions not only of society but of the police organisation as well. The last part of the article deals with the tasks of the “community police”, their marginalized position in the police organization, and the special relationship they share with their clients. It is argued that the practice of the community policemen has a significant impact on their views on crime-related issues, and that a change of practice might have considerable effect on both the views and the work of the police as a whole.